Phase change materials in building integrated space heating and domestic hot water applications: A review. (October 2022) - Nair, Ajay Muraleedharan; Wilson, Christopher; Huang, Ming Jun; Griffiths, Philip; Hewitt, Neil
Abstract: Thermal energy storage (TES) using phase change materials (PCM) has been widely investigated for various applications from very low to very high temperatures due to its flexible operating temperature range, high energy storage density, and long-life cycle at a reasonable cost. The use of PCM in building components and hot water production can reduce the building energy demand, indoor temperature fluctuation, and better demand-side management by utilising available renewable energy and off-peak electricity. This paper presents a state-of-the-art review of the application of PCM domestic thermal heating. The classifications of TES systems, advantages of PCM over other TES systems, and the methods to overcome shortcomings of PCM are discussed in brief. Then the various novel techniques employed in underfloor heating, wall heating, PCM integration in domestic hot water tanks, and developing latent heat thermal energy storage units are extensively reviewed and the major findings of the research works reviewed are tabulated. Based on the extensive review conducted, the important factors to be considered for selecting a suitable PCM for these applications are summarised, and the commercially available PCM for the above applications are listed with their major thermo-physical properties and supplier details in the appendix. Highlights: Phase change materials: bridge between the supply and demand of energy Methods to enhance the thermal performance of PCM systems State of art review on PCM application in building integrated heating and DHW production application PCM selection for building integrated heating and DHW production application